"The Performing Arts" As an Innovative and Creative Learning Mediaof Music Arts Education for PGSD Students - Sutikno, Putri Yanuarita (Proceedings of the UR International Conference on Educational Sciences, 2018)
The performing arts isa form of entertainment such as acting, dancing, and playing music in order to show artwork to other people (the general public) in order to get a response and assessment. The performance is a form of communication between the creator of art (apresian) and art connoisseurs (appreciator). This article is qualitative descriptive. Problems are found in the phenomenon of arts learning, especially music, namely the low enthusiasm and creativity of musical PGSD students in learning the art of music. Assuming that they were not art-talented students, making PGSD students feel insecure, afraid, and even shy because of the lack of musical skills in attending music arts subjects. Therefore, the performing artsis presented as solutions of innovative and creative learning media because it uses a project-based learning model or work that implements a learning strategy that is more student centered. That is, learning that provides more opportunities for students to construct knowledge independently (self-directed) and mediated by peers (peer mediated instruction) in producing project works. The purpose of making a performance is to show the ability of PGSD students to produce artwork, especially music, to learn and to appreciate the ability of others in arts, get lots of input in the form of ideas and criticisms of the works that have been made, so they can improve their weaknesses in the field of music as well as spurring them to produce better works.